PENGARUH LABELISASI HALAL TERHADAP PROSES KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH - Nisak, Ardhea Choirun (Jurnal Insani, 2020)
The development of an increasingly sophisticated and modern era brings convenience and practicality in supporting one's appearance, one of which is about the use of beauty products for women. In everyday life, most women unwittingly use cosmetics almost all the time. Currently the trend of beauty products has developed rapidly, one of which follows the aspects of Halal Life Style. Halal-labeled products are very important in Indonesia. Beauty products with halal labels on their products, are very beneficial for the majority of Indonesian people who are moeslim. One beauty product that targets Moeslim consumers in Indonesia and has proven to be halal in its products is Wardah products. This study aims to determine whether there is an effect of halal labeling on the purchase decision process of Wardah cosmetics and to determine the effect of Wardah labeling on the purchase decision process. The study was conducted with quantitative research methods with the type of descriptive research. The sampling technique used is using non-probability sampling and obtaining 452 respondents from Instagram account followers @wardahbeauty. The results showed that there was an influence between halal labeling on the purchase decision process of Wardah cosmetics. With a correlation coefficient of 0.675 the strength of the relationship is strong between halal labeling and the buying decision process.